Use of serological and molecular techniques for detection of Leptospira sp. carrier sheep under semiarid conditions and the importance of genital transmission route - Nogueira, Denise Batista (2020)
It is possible that there are peculiarities in the epidemiology of leptospirosis in regions with a semiarid climate, where the environment is often adverse, allowing the occurrence of alternative transmission routes. The objective of the work was to generate contributions to the diagnosis and epidemiology of Leptospira sp. infection in sheep reared in semiarid conditions, using serological, molecular and microbiological techniques for diagnosis in dry and rainy seasons. Samples of blood, vaginal fluid, urine, bladder, kidney, uterus, uterine tube, ovary and placenta were collected from 104 sheep (52 animals per season – dry and rainy) slaughtered in the Brazilian semiarid. Diagnostic tests performed were microscopic agglutination test (MAT), polymerase chain reaction (PCR) and bacterial isolation. Anti-Leptospira sp. antibodies were found in 26 (25%) of the animals analyzed by MAT at 1:50 dilution (cut-off 50), while 69 (66.3%) animals had at least one organ/fluid with the presence of Leptospira sp. DNA. Overall, PCR was performed on 758 fragments of organs/fluids from the genital and urinary tracts, and 519 (68.5%) samples tested positive. PCR-positivity was statistically different in dry (46.2%) and rainy (11.5%) seasons for vaginal fluid. It was possible to perform the DNA sequencing in nine samples with 99% similarity to L. interrogans and recovery of viable strains in three samples of vaginal fluid. Regardless of the biological material used in PCR to detect carrier animals and the season, the highest MAT sensitivity values were obtained with cut-off 50 compared to 100. The results obtained indicate that, even in the adverse environmental conditions of the semiarid region, leptospires may survive and propagate by alternative routes of transmission, such as sexual, and the presence of PCR-positive genital tracts in ewes suggests that sexual transmission may play an important role in the epidemiology of the disease in sheep in Brazilian semiarid. In addition, it is suggested the use of titer 50 as cut-off point at serology in semiarid conditions.